ستخدام طريقتي التدريب الفتري المرتقع الشدةوالتكراري التكراري لتطوير القوة المميزه بالسرعه للطراف السفلى وتاثيرها على سرعه الدحرجه للاعبي كرة القدم المتقدمين - عماد كاظم خليف (الرياضة المعاصرة)
Speed is the most important elements of excellence in a match and an influential factor in resolving the outcome of the game, the player owning the speed (the speed characteristic force) will help him in the speed performance of the basic skills. Research problem In the presence of slow distinctive strengths speed with the players, which negatively affect the speed of performance skills, particularly the speed of the ball and rolling. Research aims To identify the use of the two way of training “high intensity and interval training” by both the trainer and researcher, and the difference between the two approaches. Experimental method was used to design the two groups on a sample of Alsenaa players Sports Club football is made up of 24 players were divided randomly into two groups and a pilot officer in each group (12) for the player, the two methods were applied to all players of the experimental group. The application of the proposed experimental curriculum by five units continued training and the formation of (2: 3) up and down every week for six weeks.